Teachers’ Techniques in Teaching Vocabulary at the First Year Students of MTs. Asholihiyah Lopan Ketak East Lombok - Kamarudin Kamarudin (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2015)
This research deals with teachers’ techniques in teaching English vocabulary at the first year students of MTs Assholihiyah Lopan Ketak East Lombok. It is expected to serve as an attempt to contribute to more teachers’ techniques in teaching vocabulary at junior high school in especially in Assholihiyah Lopan Ketas East Lombok as well as the reference to the teachers who teach English vocabulary. It applied a qualitative approach. The subject of the research was one of English teacher. The data was collected through questionnaire and interview. The data was analyzed through data reduction, display, and conclusion. The result was the teacher of class 1 (1 and 2) used the identifying picture and categorizing object technique. And the teacher in class 1 (3) used categorizing objects technique to teach English vocabulary. Those techniques found from the textbook, so the teacher develops this technique by herself. In presenting English especially vocabulary, the teacher should be creative in choosing the material and able to stimulate the students interest.